Early Detection and Investigation of Extracellular Vesicles Biomarkers in Breast Cancer - Bandini, Erika; Rossi, Tania; Scarpi, Emanuela; Gallerani, Giulia; Vannini, Ivan; Salvi, Samanta; Azzali, Irene; Melloni, Mattia; Salucci, Sara; Battistelli, Michela; Serra, Patrizia; Maltoni, Roberta; et al. (Frontiers in Molecular Biosciences, 2021)
Breast Cancer (BC) is the most diagnosed tumor among women worldwide, and the leading cause of cancer death in female population. The percentage of patients experiencing poor prognosis along with the risk of developing metastasis remains high, also affecting the resistance to current main therapies. Cancer progression and metastatic development are no longer due entirely to their intrinsic characteristics, but are also regulated by signals derived from cells of tumor microenvironment. Extracellular vesicles (EVs) packed with DNA, RNA, and proteins, are the most attractive targets for both therapeutic and diagnostic applications, which represent a decisive challenge as liquid biopsy-based markers. Here we performed a case study based on a multiplexed phenotyping cytofluorimetric approach to characterize BC-derived EVs from BC patients and cell lines, through the detection of multiple antigens. Our data reveal the expression of EVs-related biomarkers derived from BC patient plasma and cell line supernatants, suggesting that EVs could be utilized for characterizing and monitoring disease progression.